Effect of Soaking Time for Eggs with Brown Seaweed Extract (Sargassum Crassifolium) for Purebred Chicken Eggs - Azani Saputra; Manjula T; Katarzyna Chojnacka (Frontier Advances in Applied Science and Engineering, 2023)
The main objective of this study was to investigate how different durations of soaking brown seaweed extract (Sargassum crassifolium) affect the quality of chicken eggs in terms of their safety and sensory characteristics. The research utilized an experimental design with a one-factor Completely Randomized Design, encompassing five different time intervals: 0 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, and 70 minutes of soaking the eggs in S. crassifolium extract, each with three replications. The parameters that were assessed included the microbiological quality, specifically the total microbe count, APM coliform count, APM E. coli count, and the presence of Salmonella sp. Additionally, the organoleptic quality, focusing on the appearance and aroma of the eggs, was also evaluated. The collected data was subjected to a variance analysis (Analysis of Variance) at a significance level of 5%, using CoStat software. In cases where a significant difference was detected, post-hoc tests such as the least significant difference (LSD) for the total microbial parameters and the Honest Significant Difference (BNJ) for the organoleptic parameters were performed to identify specific variations among the different soaking time intervals. The results of the study demonstrated that an extended soaking time of 70 minutes in S. crassifolium extract had a notable impact. It significantly reduced the total microbial count on the eggshells by 5.5671 Log CFU per shell, lowered the coliform count to 11.07 APM per shell, resulted in an E. coli count below 3.0 APM per shell, and effectively eliminated Salmonella sp.